Characterization of the lower layer in the dayside Venus ionosphere and comparisons with Mars. (November 2015) - Girazian, Zachary; Withers, Paul; Häusler, Bernd; Pätzold, Martin; Tellmann, Silvia; Peter, Kerstin
Abstract: The influence of solar zenith angle (SZA) and solar irradiance has been well characterized for the V2 layer in the Venus ionosphere, but not the V1 layer, where previous efforts were limited by data scarcity and incomplete SZA coverage. Here we use more than 200 radio occultation profiles from Venus Express with good SZA coverage to characterize how the V1 peak altitude, peak density, and morphology respond to changes in SZA and solar activity. The V1 and V2 peak altitudes vary little with SZA, and both peak electron densities vary with SZA in an approximately Chapman-like manner. These results imply that the thermal structures of the atmosphere and ionosphere between ∼125 km and ∼140 km vary little with SZA. As solar activity increases, the ratio of the V1 to V2 peak density increases, and the V1 morphology changes more than the V2 morphology. These results are due to the soft X-ray flux increasing relative to the EUV flux as solar activity increases. We compare the behavior of the V1 layer to the analogous M1 layer at Mars, and find that their peak altitudes respond differently to changes in SZA and solar activity. The V1 peak density also increases more with solar activity than the M1 peak density. These distinct behaviors arise from differences in their underlying neutral atmospheres. Abstract : Highlights: V1 and V2 peak altitudes vary little with solar zenith angle. V1 and V2 peak densities vary with solar zenith angle in a Chapman-like manner. The ratio of the V1 to V2 peak density increases with solar activity. We compare the behavior of the V1 layer at Venus to the M1 layer at Mars.